The Role of Multiple Intelligences Theory in Learning - Aris Kusmiran Winandar; Unan Yusmaniar Oktiawati; Winantu Winantu; Petit Emily; Spradlin Sunil (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Mutiple intelligences or what is commonly referred to as multiple intelligences, this intelligence is a benchmark for knowing how to solve problems. Mutiple intelligences also measure thinking ability and intellectual development. Therefore, Mutiple intelligences must be applied because this intelligence serves to train and assist in formulating problems and ways to make choices. This study aims to determine the extent to which the implementation of Mutiple intelligences in learning moral creed. This type of research is quantitative, based on data collection, analyzing and displaying data, and interviews. For data collection techniques and interviews conducted online to several teachers, and the data will be displayed in tabular form. The result of this research is to find out whether Mutiple intelligences in learning moral creed has been applied in learning moral creed learning itself. The limitation in this research is that the observations are not carried out thoroughly to all teachers of moral creed learning and interviews are not conducted directly. Based on the results of this study, it is hoped that future researchers will be able to collect data thoroughly so that the results of the observation are more detailed, and can conduct interviews directly without any intermediaries.